Comparison of Bone Grafts From Various Donor Sites in Human Bone Specimens. Issue 6 (September 2018) - Kamal, Mohammad; Gremse, Felix; Rosenhain, Stefanie; Bartella, Alexander K.; Hölzle, Frank; Kessler, Peter; Lethaus, Bernd
Abstract : Abstract: The objective of the current study was to compare the three-dimensional (3D) morphometric microstructure in human cadaveric bone specimens taken from various commonly utilized donor sites for autogenous bone grafting. Autogenous bone grafts can be harvested from various anatomic sites and express heterogeneous bone quality with a specific 3D microstructure for each site. The long-term structural integrity and susceptibility to resorption of the graft depend on the selected donor bone. Micro-computed tomography generates high-resolution datasets of bone structures and calcifications making this modality versatile for microarchitecture analysis and quantification of the bone. Six bone specimens, 10 mm in length, where anatomically possible, were obtained from various anatomical sites from 10 human dentate cadavers (4 men, 6 women, mean age 69.5 years). Specimens were scanned using a micro-computed tomography device and volumetrically reconstructed. A virtual cylindrical inclusion was reconstructed to analyze the bone mineral density and structural morphometric analysis using bone indices: relative bone volume, surface density, trabecular thicknesses, and trabecular separation. Calvarial bone specimens showed the highest mineral density, followed by the chin, then mandibular ramus then the tibia, whereas iliac crest and maxillary tuberosity had lower bone mineral densities. The pairwise comparison revealed statistically significant differences in the bone mineral density and relative bone volume index in the calvaria, mandibular ramus, mandibular symphysis groups when compared with those in the iliac crest and maxillary tuberosity, suggesting higher bone quality in the former groups than in the latter; tibial specimens expressed variable results.